The Use of Video Blog Posted in YouTube for Teaching Spoken Recount Text - Awalia, Rizki Novita; Apriliaswati, Rahayu; Rahmani, Eka Fajar; Sudarsono; Wardah (Kirana Publisher (KNPub), 2023)
This research was conducted to investigate the effect of video blog posted in YouTube to teach spoken recount text to the secondary students. The design was the one group pretest posttest design of pre-experimental study. The sample, X MIPA 2 of SMA Negeri 2 Pontianak, was chosen from cluster random sampling technique totaling 30 students. The findings indicate that there is a significant effect of video blog posted in YouTube towards the students’ ability in spoken recount text. The t-test calculation was 25.92 which was higher than t-table 2.045 (df=29; significance α=0.05). Meanwhile, the effect size was 4.41 categorized as strong effect. From these results, it was revealed that the Ho was rejected while the Ha was accepted. Therefore, it can be concluded that video blog posted in YouTube was effective to teach spoken recount text to secondary students, especially the tenth-grade ones. Thus, the researchers recommend this technique to be used as one of alternatives to teach spoken recount text, specifically related to people’s experience.